The Effectiveness of Educational Games to Improve Students' Arabic Mufrodat Mastery: A Meta-Analysis Study - Lailaa, Hikmatul; Mariah, Enung (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2025)
The purpose of this study was to measure the effectiveness of educational games in improving students' Arabic mufrodat skills. The method used was a meta-analysis of 13 primary studies that met the inclusion criteria, with data analysis using Comprehensive Meta-Analysis (CMA) software and a random effects approach. The results indicate a combined effect size of g = 1.375 (p < 0.01), indicating a very large effect of educational games compared to traditional learning models. Moderator variable analysis shows that the impact of educational games does not differ significantly based on sample size, educational level, publication year, or type of game. Therefore, educational games have proven to be highly effective in improving students' Arabic vocabulary skills. Further research is recommended to investigate variations in game types and broader application contexts to strengthen the generalizability of these results.